Evaluating Inflow Result from SWAT Model at Singkarak Lake Under Limited Data. Issue 1 (1st July 2022) - Wibowo, H; Ridwansyah, I; Rahmat, A
Abstract: Sustained lake functioning requires proper management in the catchment area and the water body. To address this, information on lake water balance is crucial because it is the basis for many scientific investigations of processes that occur in lake ecosystems. In many lakes, inflow from catchment areas is dominated by river flow. The problem is that inflow measurement data on rivers into the lake are difficult to obtain. Several models are used for inflow estimation, but validation will undoubtedly be complex because there is no observational data. The approach taken is to analyze the model results' inflow accuracy through water balance analysis based on observational data on water level, climatology, and outflow. This approach will be implemented on Singkarak Lake, 109.08 km 2, which is a tectonic lake located in West Sumatra. The method used to calculate inflow uses the SWAT hydrological model based on land use data in 2014 and Chirps rainfall in the 2010-2019 period. Water balance analysis is used to evaluate the inflow of the model results based on observational data on water level and outflow. The results show that the monthly inflow is too high, with an average excess of 6.21cms, which causes the average water level to be 0.52 meters higher.